Innovative Methodological Instrument for Quantification of Professional Risk Specific to Complex Systems of Work - Gabriel Vasilescu; Mihail Vătăsescu; Passca Mihaela; Ciprian Jitea (The Global Environmental Engineers, 2014)
This paper presents research on estimating and assessing occupational risks to secure specific activities in the presence of hazards of industrial work systems, and is based on a thorough knowledge of interdisciplinary concepts from various fields related to systems security engineering.